2004
DOI: 10.1145/1024338.1024378
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive activities of abstraction in object orientation

Abstract: Alongside the widespread support for adopting object orientation there are reports on difficulties in learning object oriented programming and design. This indicates the need for refining the research on cognitive difficulties in a way that will offer guidelines for better designing respective education. The presented findings of our study relate to general issues of object-oriented design and in particular to the abstraction issue with its various manifestations. Based on students' solutions we extracted a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 10 publications
9
38
0
Order By: Relevance
“…The students had difficulties in exhibiting high levels of assimilation concerning a proper design for a hierarchy of exceptions. These results are in line with previous research regarding the object-oriented design capabilities of novice programmers (Lavy et al, 2009;Or-Bach & Lavy, 2004;Sim & Wright, 2001). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The students had difficulties in exhibiting high levels of assimilation concerning a proper design for a hierarchy of exceptions. These results are in line with previous research regarding the object-oriented design capabilities of novice programmers (Lavy et al, 2009;Or-Bach & Lavy, 2004;Sim & Wright, 2001). …”
Section: Discussionsupporting
confidence: 92%
“…In addition, to be able to construct an adequate class hierarchy, the student must demonstrate a high level of abstraction. Previous research has shown that few students are able to do this (Lavy, Rashkovits, & Kouris, 2009;Or-Bach & Lavy, 2004). …”
Section: Machineoperationexception)mentioning
confidence: 99%
“…The students had difficulty exhibiting high levels of understanding concerning the following: use of multiple exceptions; flow of control in the context of exceptions; handling exceptions further up the calling chain; catching and handling hierarchically related exceptions; and overriding methods that throw exceptions. These results are consistent with previous research regarding the object-oriented design capabilities of novice programmers (Lavy, Rashkovits, & Kouris, 2009;Or-Bach & Lavy, 2004;Sim & Wright, 2001). …”
Section: Discussionsupporting
confidence: 92%
“…The concepts of class hierarchy and method override are part of the object-oriented paradigm which necessitates a certain level of abstraction and hence is difficult to comprehend (Or-Bach & Lavy, 2004;Sim & Wright, 2001). Also the fact that when an exception is thrown the control is passed to the nearest catch clause up the calling chain requires a profound understanding of the fundamentals of computing (memory stack, flow of control, etc.)…”
Section: Perceptions Concerning the Complexity Of The Exception Mechamentioning
confidence: 99%
“…Many graduating students turn out to be unable to create a proper software design [14,25]. Students struggle with the application of concepts such as abstraction and polymorphism [28] and information hiding [16]. These findings suggest that a form of scaffolding of students' learning is in order, so the question arises what kind of scaffolding is appropriate.…”
Section: Introductionmentioning
confidence: 99%